Já vi esse filme: usos do cinema no trabalho do formador de professores - Tilger, Marcos Alexandre (2016)
The following research stems from the perception that the use of cinematographic productions for educational purposes in the continuous professional development of teachers hinges on the attribution or recognition of certain characteristics which, when combined with the pedagogical work of those responsible for the training of teachers, allow them to meet the desired expectations. As such, the established goal of this research is the analysis of the determining factors for the selection of the films and for the mediation strategies used during the activities developed by these professionals. The purpose of the analysis is to comprehend how educational and formative meaning is attributed to films via preceding experiences, professional and academic knowledge as well as the knowledge that stems from the relationships between the subjects and the cultural products, and how these elements act in an interconnected fashion. For that purpose, an empirical research based on the concepts developed by the authors of the Critical Theory of Society was conducted through content analysis of semi structured interviews with four professional developers of teachers. Among the noteworthy elements for the analysis are the changes that have occurred in the job sphere throughout late capitalism, together with normative and theoretical production funded by international organizations with great influence over the Brazilian political reforms and the significant alterations in teaching policies. In light of these elements, the critical stance of this research is based on the theoretical contributions of Adorno, Horkheimer, Benjamin and Marcuse, with emphasis on the concepts of technological rationality, late capitalism, formation, experience, administered free time and culture industry. The analysis was conducted through the crossed study of analytical descriptive comparative categories and conceptual critical analytical categories, favoring a negative dialectical approach with focus on the primacy of the object. It can be concluded, based on the justifications and choices of professional developers who are guided by the need to adapt to institutional innovations, employer demands and to the teachers in development themselves, that these restraints prevent actual formative and educational experiences from taking place, and as such these professionals limit themselves to practices of sensitization, motivation and negotiation, all of which have as reference points and persuasive resources products of the culture industry